Metabolically stable apelin-analogues, incorporating cyclohexylalanine and homoarginine, as potent apelin receptor activators. Issue 8 (8th July 2021) - Fernandez, Kleinberg X.; Fischer, Conrad; Vu, Jennie; Gheblawi, Mahmoud; Wang, Wang; Gottschalk, Samantha; Iturrioz, Xavier; Llorens-Cortés, Catherine; Oudit, Gavin Y.; Vederas, John C.
Abstract : Cyclohexylalanine- and homoarginine-substituted apelin analogues are demonstrated to be metabolically stable APJR agonistic peptides with hypotensive effect. Abstract : High blood pressure and consequential cardiovascular diseases are among the top causes of death worldwide. The apelinergic (APJ) system has emerged as a promising target for the treatment of cardiovascular issues, especially prevention of ischemia reperfusion (IR) injury after a heart attack or stroke. However, rapid degradation of the endogenous apelin peptides in vivo limits their use as therapeutic agents. Here, we study the effects of simple homologue substitutions, i.e. incorporation of non-canonical amino acids l -cyclohexylalanine (l -Cha) and l -homoarginine (l -hArg), on the proteolytic stability of pyr-1-apelin-13 and apelin-17 analogues. The modified 13-mers display up to 40 times longer plasma half-life than native apelin-13 and in preliminary in vivo assay show moderate blood pressure-lowering effects. The corresponding apelin-17 analogues show pronounced blood pressure-lowering effects and up to a 340-fold increase in plasma half-life compared to the native apelin-17 isoforms, suggesting their potential use in the design of metabolically stable apelin analogues to prevent IR injury.